Aerosol physicochemical effects on CCN activation simulated with the chemistry-climate model EMAC. (August 2017) - Chang, D.Y.; Lelieveld, J.; Tost, H.; Steil, B.; Pozzer, A.; Yoon, J.
Abstract: This study uses the EMAC atmospheric chemistry-climate model to simulate cloud properties with a prognostic cloud droplet nucleation scheme. We present modeled global distributions of cloud condensation nuclei (CCN) number concentrations and CCN activation rates, together with the effective hygroscopicity parameter κ, to describe the aerosol chemical composition effect on CCN activation. Large particles can easily activate into cloud droplets, even at low κ values due to the dominant size effect in cloud droplet formation. Small particles are less efficiently activated as CCN, and are more sensitive to aerosol composition and supersaturation. Since the dominant fraction of small particles generally originates from anthropogenic precursor emissions over land, this study focuses on the influence of the continental atmosphere, using a prognostic cloud droplet nucleation scheme that considers aerosol-cloud interactions during cloud formation, together with a double-moment cloud microphysics scheme. The agreement of simulated clouds and climate with observations generally improves over the Northern Hemisphere continents, particularly high air pollution regions such as Eastern US, Europe, East Asia by accounting for aerosol-cloud interactions that include impacts of chemical composition on CCN activation. Highlights: Modeled κ represents aerosol composition effects (e.g., hygroscopicity) on cloud formation. A prognostic cloud droplet nucleation scheme accounts for aerosol-cloud interactions. Simulated CCN shows decreased aerosol composition effects by increasing particle size. The modeling result of a prognostic nucleation scheme is improved over air-polluted regions.